Natalizumab in Multiple Sclerosis Treatment: From Biological Effects to Immune Monitoring - Khoy, Kathy; Mariotte, Delphine; Defer, Gilles; Petit, Gautier; Toutirais, Olivier; Le Mauff, Brigitte (Frontiers in Immunology, 2020)
Multiple sclerosis is a chronic demyelinating disease of the CNS with an autoimmune component. Among the recent disease-modifying treatments available, Natalizumab, a monoclonal antibody directed against the VLA-4 integrin, is a potent inhibitor of cell migration towards the tissues including CNS. It potently reduces relapses and active brain lesions in the relapsing remitting form of the disease. However it has also been associated with a severe infectious complication, the progressive multifocal leukoencephalitis. Using the standard protocol with an injection every 4 weeks it has been shown by a close monitoring of the drug that trough levels soon reach a plateau with an almost saturation of the target cell receptor as well as a down modulation of this receptor. However, in case of permanent anti-natalizumab immunisation, the drug is quickly removed and treatment is inhibited sometimes without obvious symptoms. When treatment is interrupted, the drug persisted both free and bound to the cell for 8 to 16 weeks suggesting that it might be possible to increase the interval between injections. In order to optimise the treatment and maintain efficacy while potentially limiting the risk of PML, or to switch to another treatment in case of immunisation some biological parameters useful for treatment monitoring are discussed